Penerapan Plot Linear terhadap Perkembangan Cerita dalam Film Dua Hati Biru Karya Sutradara Gina S. Noer - Jenny Fransiska; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Film is a medium that functions as entertainment and an effective means of communication in conveying messages, stories and emotions to the audience.